A systematic review and meta-analysis of neuroticism and anxiety during the COVID-19 pandemic - Regzedmaa, Enkhtuvshin; Ganbat, Mandukhai; Sambuunyam, Munkhzul; Tsogoo, Solongo; Radnaa, Otgonbayar; Lkhagvasuren, Nasantsengel; Zuunnast, Khishigsuren (Frontiers in Psychiatry, 2024)
Introduction In response to the global impact of the COVID-19 pandemic, concerns about mental health, particularly anxiety levels, have become prominent. This study aims to explore the relationship between neuroticism, a personality trait associated with emotional instability, and anxiety during the COVID-19 outbreak. Methods A comprehensive literature search was conducted using the Cochrane Library, HINARI, Google Scholar, and PUBMED, resulting in the identification of 26 relevant papers. The study protocol has been registered with PROSPERO under the number CRD42023452418. Thorough meta-analysis was performed using Comprehensive Meta-Analysis V4 software. Results Meta-analysis revealed a significant positive relationship between anxiety and neuroticism, with 26 studies supporting this association (OR = 3.213, 95% CI 2.352 to 4.391). The findings underscore the importance of considering personality traits, particularly neuroticism, in understanding psychological responses to major global crises such as the COVID-19 epidemic. Discussion The observed connection between neuroticism and heightened anxiety levels emphasizes the need for targeted interventions, especially for individuals with high levels of neuroticism. Further research into potential therapeutic approaches for mitigating anxiety consequences in the context of a significant global catastrophe is warranted. Systematic Review Registration https://www.crd.york.ac.uk/prospero/#CRD42023452418.